Effect of epidural labor analgesia on maternal and infant outcomes in parturients with gestational diabetes mellitus—A prospective cohort study - Li, Gehui; Qi, Xiaofei; Tan, Xuhong; Wu, Mingguang; Wang, Hao; Wen, Ping; Huang, Xiaolei; Li, Yuantao (Frontiers in Pediatrics, 2022)
Abstract Background: The occurrence of gestational diabetes mellitus (GDM) is caused by a variety of factors and associated with increased risks of several adverse outcomes for both mothers and infants. However, the effects of epidural labor analgesia in parturients with GDM on maternal and infant outcomes have not been characterized. Methods: According to parturients’ choice, they were divided into the epidural group (n=133) and no epidural (control) group (n=135). Data for relative variables in the perinatal period were collected, and the potential associations of epidural labor analgesia with infant outcomes were analyzed by univariate analysis and multivariate logistic regression analyses. Results: The rate of neonatal admission to the neonatal intensive care unit (NICU) for hypoglycemia was higher in the epidural group (7.52%) than in the control group (1.48%; p<0.05). Epidural labor analgesia and drug-based diabetes control were independent predictors of the rate of neonate transfer to the NICU for hypoglycemia. Conclusion: Epidural labor analgesia was associated with an increased risk of neonatal transfer to the NICU for hypoglycemia. Thus, monitoring of neonatal blood glucose levels after administration of epidural labor analgesia in parturients with GDM may be beneficial. Trial registration: The study was registered in the China Clinical Registration Center (Registration No. ChiCTR-OOC-17013164, Registered on 30 October 2017).